Tinjauan Ketepatan Penjajaran Rekam Medis Di Rumah Sakit Umum Daerah Kembangan - Fauziah Irfany; Lily Widjaja; Laela Indawati; Deasy Rosmala Dewi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Alignment is the process of aligning medical records in the storage room according to the system used. The medical record storage system at Kembangan Hospital uses centralization, the medical record numbering system uses the Unit Numbering System (UNS) and the alignment system uses Terminal Digit Filing (TDF). The aim of this research is to determine the accuracy of medical record alignment. This research used a descriptive method with a quantitative approach, the population was 293 medical records using a saturated sample. From the results of research on the primary digit 07 storage shelf, it was found that there were inaccuracies in the alignment of 162 medical records (55%). This alignment inaccuracy was divided into three digits, namely 34 medical records (21%) had the 1st digit incorrect, 85 medical records (52%) had the 2nd digit incorrect and 43 medical records (27%) had the 3rd digit incorrect. . It was found that the cause of the alignment error was due to human error, the unavailability of a tracer and the map not using color coding. Medical records that cannot be found can be traced by looking at the patient's history of treatment at Simrs Khanza, then looking for the first digit number that is being searched for. When a medical record is not found, a search for the accuracy of the alignment of the medical record is carried out using the medical record tracking method. If a medical record cannot be found, a new medical record will be used temporarily.